Multiple topical product dermatitis: Paradigms in understanding and future perspectives - Sean E. Mangion; Antti Mikkonen; Lorraine Mackenzie; Michael S. Roberts; Howard I. Maibach (Wiley, 2024)
Abstract It is common for people to be exposed to multiple topical products daily, either through cosmetics, personal care or drug formulations. This increases the possibility of contact dermatitis and poses a major challenge for treatment as well as the design and regulation of safe and effective topical products. Here, we define the scope of the problem of multiple topical product dermatitis and highlight a strategy for differential diagnosis. The tools currently available for prediction of skin reactions are also discussed along with further work required to improve our ability to (1) identify irritant or sensitising agents and (2) prevent dermatitis occurrence.